TELAAH OTORITAS KERASULAN PAULUS TERHADAP TUDUHAN KAUM MUSLIM MENURUT SURAT GALATIA 1:1-5 - Lawolo, Aprianus; Wijaya, Hendi (P3M STT Kristus Alfa Omega, 2022)
Today, the complex issue of Paul's apostolic authority has become a hot topic both among Christian theologians and among Islamic polemicists. To answer the problems, the authors use the exegesis method of Galatians 1:1–5 and literature studies to find sources that are relevant to the existing problems. The results of this study indicate that Paul was legally chosen by God and had the same task and function as the other apostles, namely, to proclaim the resurrection of Christ.